2020
DOI: 10.3389/fchem.2020.00812
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights Into the Anticancer Properties of the Auranofin Analog Au(PEt3)I: A Theoretical and Experimental Study

Abstract: Au(PEt 3)I (AF-I hereafter), the iodide analog of the FDA-approved drug auranofin (AF hereafter), is a promising anticancer agent that produces its pharmacological effects through interaction with non-genomic targets such as the thioredoxin reductase system. AF-I is endowed with a very favorable biochemical profile showing potent in vitro cytotoxic activity against several cancer types including ovarian and colorectal cancer. Remarkably, in a recent publication, some of us reported that AF-I induces an almost … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 75 publications
0
26
0
Order By: Relevance
“…Although these outcomes might represent a limitation to the employment of non-bonded topological schemes for the description of Pb(II) coordination by sulfur ligands, it should be also taken into account that the binding of thiol at metal centers may often be followed by deprotonation, leading to the corresponding thiolate complex. Several theoretical and experimental evidences have confirmed that a marked decrease of the thiol pKa occurs upon coordination at even soft metal centers such as Au(I) [66][67][68][69], Au(III) [70] and also Pb(II) [23]. Thus, the use of empirical force field implemented with non-bonded potentials describing the Pb(II) coordination at sulfur ligands may still be considered valuable by assuming the thiolate, and not thiol, as the metal-binding form.…”
Section: Discussionmentioning
confidence: 99%
“…Although these outcomes might represent a limitation to the employment of non-bonded topological schemes for the description of Pb(II) coordination by sulfur ligands, it should be also taken into account that the binding of thiol at metal centers may often be followed by deprotonation, leading to the corresponding thiolate complex. Several theoretical and experimental evidences have confirmed that a marked decrease of the thiol pKa occurs upon coordination at even soft metal centers such as Au(I) [66][67][68][69], Au(III) [70] and also Pb(II) [23]. Thus, the use of empirical force field implemented with non-bonded potentials describing the Pb(II) coordination at sulfur ligands may still be considered valuable by assuming the thiolate, and not thiol, as the metal-binding form.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we assessed seven among the routinely employed and recently developed density functionals for their capability to predict the structure and reactivity of Cl-Pt(NH = C(CH 3 )-O) 2 As(OH) 2 , arsenoplatin (AP), in order to point out the adequate level of theory to use in future investigations on its mechanism of action. In particular, we considered the widely used hybrid GGA functional B3LYP [44,45] and its variant including Grimme's empirical dispersion correction B3LYP-D3 [46], the meta-GGA functional originally designed to study transition metal complexes M06-L [47], the Minnesota hybrid meta-GGA functional M06-2X [48], the one-parameter hybrid GGA functional PBE0 [49] and two more recent range-separated hybrid functionals which have been shown to provide good results for transition metal systems CAM-B3LYP [50] and ωB97X [51], which are known to give a good description of geometries and reaction profiles for transition or heavy metal-containing compounds [52][53][54][55][56], including structure and reactivity of transition metal complexes [57,58], and particularly antitumor Pt-based compounds [32,[59][60][61]. We also considered the influence of the use of three basis sets differing in their size and for the number of polarization and diffuse functions.…”
Section: Introductionmentioning
confidence: 99%
“…It is now widely recognized that the pharmacologically active portion of the AF molecule is the cationic fragment [Au(PEt 3 )] + (Pratesi et al 2018 ; Zoppi et al 2020 ) while the thiosugar moiety mainly acts as a carrier ligand improving the bioavailability and the gold complex pharmacokinetic profile when orally administered (Marzo et al 2017 ). Based on these arguments, recently, we started a systematic and comparative evaluation of a series of AF-related compounds (Marzo et al 2017 , 2018 ; Tolbatov et al 2020 ). Our attention was firstly focused on AF-related complexes where the thiosugar moiety is replaced by halide ligands.…”
Section: Introductionmentioning
confidence: 99%